Keputusan Pembelian melalui E-Service Quality dan Pemasaran Media Sosial: Peran Mediasi Brand Image pada Zara di Kota Semarang - Eldina, Sheila; Damar, Haunan; Safitri, Maria; Fatmawati, Elia Resha (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The increasing use of digital platforms in shopping activities has encouraged companies to improve the quality of their e-services and social media marketing strategies to influence consumer purchasing decisions. This study aims to analyze the influence of e-service quality and social media marketing on purchasing decisions with brand image as a mediating variable for Zara products. This study uses a quantitative approach with a survey method. The research sample consisted of 190 respondents who were Zara consumers and were selected using a purposive sampling technique. Data collection was carried out through a questionnaire with a Likert scale, then analyzed using the Structural Equation Modeling (SEM) method. The results of the study indicate that e-service quality and social media marketing have a positive and significant effect on brand image. Brand image also has a positive and significant effect on purchasing decisions. In addition, the results of the mediation test prove that brand image plays a significant mediator in the relationship between e-service quality and social media marketing on purchasing decisions. These findings confirm that improving digital service quality and the effectiveness of social media marketing can strengthen brand image, which ultimately encourages increased consumer purchasing decisions for Zara products.